Fähigkeiten im analogen Denken bei mathematisch begabten Kindern: Begriffsklärung und Überblick zu empirischen Studien (mathematica didactica, 2013)
For disambiguation three categories of analogical thinking will be distinguished, viz. analogical assigning, analogical comprehension and analogical problem solving. Furthermore a differentiation of the terms “analogical thinking” and “transfer” will take place, whereupon the transfer is understood as a use of analogy, which can occur in the context of analogical assigning or analogical problem solving. Subsequently a presentation of various studies referring to the three named categories was carried out. The respective results of the studies suggests the assumption that primary school pupils who are potentially mathematically gifted stand out due to particular skills at analogical assigning and analogical problem solving.